Evaluation of gene expression and immune system of swine after consumption of biofortified milk with n-3 and n-6 - Reis, Leriana Garcia (2023)
Dietary supplementation with low ratio of n-6 and n-3 polyunsaturated fatty acids (PUFA) can decrease the risk of many of the chronic disease, the cardiovascular disease, cancer, inflammation, obesity, and autoimmune disease consequently benefiting health. This study aimed to investigate the potential health benefits of supplementing sows\' diets with cows milk biofortified with n-3 or n-6 polyunsaturated fatty acids, utilizing 8.26, 7.92, and 2.72 n-6/n-3 ratios, and on sow and their offspring. Furthermore, the study placed emphasis on several crucial elements, such as the regulation of gene expression in the liver to control lipolysis, lipogenesis, and the regulation of appetite in the hypothalamus. Also, alterations in the production of immunoglobulins, interleukins, and eicosanoids that influence the immune system were examined. Additionally, changes in the hemolytic activity of the alternative pathway of the complement system were investigated. Another objective of the study was to examine the impact of dietary changes in circulating fatty acids in the organism, colostrum and milk. Sows fed milk biofortified with n-6 and n-3 PUFA had an increased total number of embryos, greater backfat thickness in earlier gestation, altered plasma fatty acids profile, reduced IgG in colostrum, and the piglets had higher concentration of IgA, IgM and TNF-α, with lower IL-10. Sows supplemented with n-6 PUFA compared to n-3, had lower very low density lipoproteins (VLDL) and TNF-α in circulation. Whereas offspring of n-6 versus n-3 supplemented sows had lower IL-10 in circulation and lower levels of SREPB-1 mRNA in plasma. N-6 and n-3, also, enhanced sow backfat thickness from D40 to D107 of gestation, the arachidonic acid (ARA) levels in milk, viability 1 of piglets, and IgA in piglets plasma. The findings provide valuable insights into the potential health benefits of dietary supplementation with biofortified milk in swine, which can be used as a model study for humans, contributing to a better understanding of the relationship between nutrition, gene expression, immune function, and trans-generational effects, potentially leading to improved dietary recommendations and interventions for both human and animal populations.